Workshop in Hoima, Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The Hoima site is located in western Uganda near Lake Albert. The site is a productive region and diverse in crop production. We counted more than 30 crops in the workshop and identified many changed practices during recent years to improve production. However, during the workshop, farmers reported that rainfall has been erratic and that land is less productive. Photos: Anton Eitzinger (CIAT).